AN EMPIRICAL EVALUATION OF CUSTOMER PERCEPTIONS ON COMPLAINT REDRESSAL MECHANISMS ACROSS DEMOGRAPHIC SEGMENTS IN THE BANKING SECTOR - Khanna, Bala (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper studies the Customers perspective towards grievance redressal systems in Indian Bank Industry. The data collected from 300 respondents are used in the research to determine the constituents of the assurance, access and reliability. The results indicate that customers believe that the assurance, accessibility and reliability of the grievance lodging mechanism is moderate. In addition, there were statistically significant variations in the perception based on gender, marital status, training level and age. The findings have implications for banks on how they perceive customer expectations and how they can improve on handling customer complaints. The research indicates that, there is a strong need for an efficient and personalised complaint handling process, as well as for further improvement in the accessibility and transparency of procedures. The result also highlights the necessity of banks in terms of training of staff, providing the clear and full information and timely impact and resolution of customer complaints. The study adds to our understanding regarding customer satisfaction and provides managerial implications to improve the grievance redressal process. Further study may also investigate big data, culture, and the roles of social media.